Djevelens finger - Resløkken, Åmund Norum (Tidsskrift for kulturforskning, 2021)
This article discusses the agency of a museum object, "Djevelens finger" (The Devil’s finger), a model of a finger from the middle ages exhibited in the Domkirkeodden museum, Hamar. The finger has a story of a curse connected to it, a story that to a large degree gives it its agency. In discussing this object through Ervin Goffman’s "frame analysis" and Karen Barad’s "intra-active framework" I show how the notion of agency given to it, as an example of "modern superstition", is framed by an oscillation between different frameworks and is thus given meaning, in the same move, through different notions of cause and effect.